Can the critical-care pain observation tool (CPOT) be used to assess pain in delirious ICU patients? - Rijkenberg, Saskia; van der Voort, Peter H. J. (Journal of Thoracic Disease, 2016)
Critically ill patients frequently experience both procedural pain and pain at rest. Chest tube removal, tracheal suctioning, wound care, turning and arterial line insertion have been shown to be the most painful procedures (1,2).